Liposomal silibinin as a potential radioprotector of human lymphocytes in the treatment of non-small cell lung cancer - Nguyễn, Thị Huỳnh Nga (2022)
This study aimed to investigate the radioprotective effect of liposomal silibinin (Lip-SIL) on human lymphocytes in the treatment of non-small lung cancer cells using a combined method of cell viability assay and cytokinesis-block micronucleus assay for a better evaluation of whether one active compound is suitable to be used as a radioprotector in radiotherapy or not. Materials and Methods: Firstly, Lip-SIL was prepared by the lipid film hydration method combined with sonication. Secondly, penetration of Lip-SIL into cells was observed by fluorescence microscopy. Finally, the potential application of Lip-SIL as a radioprotector of human lymphocytes in the treatment of non-small cell lung cancer was evaluated using the above combined method with A549 cell line as a model. Results: The successfully prepared Lip-SIL had a spherical shape and good physical characteristics (particle size of approximately 83.9 nm, zeta potential of -20.6 mV, encapsulation efficiency of 28.8 % and payload of 5.1 %). At a SIL concentration of 10 μg/mL, Lip-SIL exhibited the highest radioprotection for lymphocytes, but showed no radioprotection or even increased genotoxicity in human lung cancer A549 cells. Conclusion: Lip-SIL is a potential protector of human lymphocytes during radiotherapy in the treatment of non-small lung cancer. Moreover, the results of this study also imply that the radioprotection ability of bioactive compounds for normal cells is not only based on their scavenging activity on reactive oxygen species (ROS) but also on their mechanisms of intracellular activations.